EFFICIENCY OF USING MULTIMEDIA COURSES IN THE EDUCATION SYSTEM - Alibekov Sayfulla Abdug‘aniyevich (Scholar Express Journal, 2022)
This article focuses on the education system in our country, the current reforms in the field of information technology, the role and importance of the organization and use of multimedia training courses in education.
Keywords: Information; Software; Innovative Activity; Communication